T(2)-FLAIR Mismatch Sign Is Caused by Long T(1) and T(2) of IDH-mutant, 1p19q Non-codeleted Astrocytoma - Kinoshita, Manabu (Magn Reson Med Sci, 2020)
T(2)-fluid-attenuated inversion recovery images (FLAIR) mismatch sign is now known to be a specific yet insensitive image feature for IDH-mutant, 1p19q non-codeleted astrocytoma. The current study revealed that lesion presenting T(2)-FLAIR mismatch exhibited extremely long T(1)- and T(2)-relaxation time while T(2)-FLAIR matched lesions showed low to moderate values. On the other hand, IDH-wildtype tumors presented noticeably short T(1)- and T(2)-relaxation time. These different relaxation time characteristics seemed to render T(2)-FLAIR mismatch sign of becoming such a unique and specific image feature for IDH-mutant, 1p19q non-codeleted astrocytoma.